Settler colonialism and the rhetoric of voluntary migration in Gaza - Ghassan Elkahlout (17906894) (2025)
This article examines the forced displacement of Palestinians in Gaza as a core mechanism within Israel’s settler-colonial strategy. Drawing on historical analysis, international legal instruments and original qualitative research, the study analyses how Israeli policies employ military force, structural deprivation, and legal manipulation to facilitate Palestinian expulsion, presented under the rhetoric of voluntary migration. By tracing the evolution of displacement from the early Zionist movement to the current genocide (This paper uses ‘genocide’ for the current Israeli assault on Gaza and ‘Naksa’ (Arabic for catastrophe/setback) for the six-day war in 1967, reflecting their systemic nature.) in Gaza, the article highlights the enduring logic of elimination embedded within settler-colonial practices aimed at erasing Palestinian presence while deflecting legal accountability. The study also engages comparative insights from other cases where displacement and demographic restructuring have been used to consolidate political control, including the experiences of Indigenous communities in North America, South Africa’s apartheid regime, and territorial fragmentation in Northern Ireland. In addition to archival and legal sources, the analysis incorporates first-hand testimonies drawn from 82 interviews with Palestinian families evacuated to Qatar since October 2023. These findings contest prevailing narratives of voluntary migration and underscore the urgency of addressing displacement as part of a broader system of structural violence and settler-colonial domination. Other Information Published in: Third World Quarterly License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/01436597.2025.2573849